Large scale societal transitions in the past - Marina Fischer-Kowalski; Daniel Hausknost (WWWforEurope, 2014)
WP 201 takes a historical perspective in analysing past systemic social-ecological transition processes. The research paper (MS 27) emerging from task 201.2 explores two major energy transitions of the past: the transition to the use of fossil fuels (e.g. starting with coal in the UK in the 17th century, and continuing in the rest of the world with coal and oil since). How was this transition linked to major institutional transformations, frequently paved by revolutions? We statistically demonstrate how similar processes occurred in many countries, and accellerated over time. In contrast to more common approaches, we do not focus on the introduction of particular technologies, but on the gradual substitution of biomass as the key source of energy by fossil fuels, and also on the increase in the amount of economically available energy. Beyond the common indicator TPES (total primary energy supply) we use and expand our historical database that countains the indicator DEC (domestic energy consumption). DEC encompasses, beyond TPES, also the energy converted by human and animal nutritional intake. We analyse the role of revolutions for the respective energy transition statistically and are able to identify statistical breaks in population growth, energy consumption and economic growth linked to the occurrence of revolutions. We compare trajectories of European and Non-European countries, and we compare countries in which the transition to the use of fossil fuels was marked by revolutionary processes with countries where this was not the case. Particular attention is paid to the phase of the transition in which revolutions have occurred, and the impact this shock had on the further course of the energy transition and on economic growth. The second marked transition analyzed occurred in the mature industrial economies in the early 1970s, in association with the first and second oil price shocks. In practically all mature industrial countries, there was triggered a termination of the steep incline of metabolic rates in favour of a fairly stable per capita level of energy and materials consumption, while economic growth continued. We investigate the policy responses in key policy areas coping with these "shocks" and achieving a reduction of biophysical growth while maintaining growth in the economy and employment. We employ a number of different methods for this analysis: we investigate long time series data statistically to explore at what time and in what sequence certain trends changed. On the other hand, we explore policy analysis literature for a number of countries qualitatively. Finally, we synthesize what can be learned from such macro societal transitions: what role do external shocks, structural change and energy policies play? Which lessons are to be learnt from past transitions in order to be in a better position to manage the transition ahead of us?
Keywords: Q01; Q02; Q28; Q32; Q34; Q38; Q43; Q48; Q5; 330; Academic research; Biophysical constraints; Demographic change; Ecological innovation; Economic growth path; Economic strategy; Energy transitions; Globalisation; Holistic and interdisciplinary approach; Industrial innovation; Industrial policy; Innovation policy; Institutional reforms; Labour markets; New technologies; Policy options; Post-industrialisation; Socio-ecological transition